Information and Communication Technologies in state public schools in the city of Coremas-PB (Research, Society and Development, 2020)
Currently, technological elements are present in every conceivable environment in society, growing exponentially also in the educational field. The insertion of technology in the school still faces some resistance due to the lack of technical preparation of the users of these resources. Thus, this research aims to present an overview of the use of Information and Communication Technologies (ICTs) in schools in the state school system in the city of Coremas-PB. Another issue raised was the verification of the possibility of these schools providing a basic computer course, using the physical and human resources existing in the institutions themselves. The research had as universe of analysis to the state schools that work in the city of Coremas. The study used field research of the descriptive type with a qualitative-quantitative approach. In view of what was raised, it was concluded that despite the fact that schools have sufficient technological apparatus to promote teaching through ICTs, the deficiency detected was in the human issue, since the teachers did not have sufficient technical knowledge to operationalize the available technological resources, as well becoming an obstacle to its use. Given the above, it was proposed that schools use their own computer labs and IT support staff to offer a basic computer course to the institution's teachers, thus enabling the future transmission of knowledge to students through these means considered more attractive. and consequently provide more meaningful learning to that student class.